Temporal dynamics of climate finance and emission reduction: Causal evidence from developing economies - Dea Fajria Tatarizqa Japal; Maisuna Kundariati (Journal of Economic Resilience and Sustainable Development, 2026)
Background: Climate change remains one of the most pressing global challenges, and climate finance has emerged as a central mechanism for supporting emission reduction and adaptation efforts in developing economies. Despite substantial commitments made under the 2021 COP26 framework, empirical evidence on the effectiveness of climate finance in mitigating greenhouse gas (GHG) emissions remains limited. Methods: This study aims to evaluate the short-run causal impact of climate finance on GHG emissions using a Regression Discontinuity in Time (RDiT) approach, with 2021 (the year of COP26) serving as the policy cutoff. The analysis employs cross-country data incorporating control variables such as gross domestic product (GDP) per capita, population, urbanization, energy use, and renewable energy consumption to isolate the independent effect of climate finance. Findings: The findings reveal that the post-COP26 period is associated with a negative but statistically insignificant change in GHG emissions, indicating that while international financial mobilization has initiated a decarbonization trajectory, its immediate effects remain modest. The results align with theoretical expectations of policy lag and absorptive capacity, suggesting that climate finance operates through gradual structural adjustments rather than abrupt reductions. Conclusion: The study concludes that the influence of climate finance is directionally consistent with emission mitigation but requires sufficient time, institutional maturity, and project implementation to materialize fully. Novelty/Originality of this article: The originality of this research lies in applying a time-based quasi-experimental design to evaluate the global effect of climate finance, offering early empirical insights into how international financial commitments translate into climate outcomes.